alpha 1-Antitrypsin deficiency is not an important cause of childhood liver diseases in a multi-ethnic Southeast Asian population - Lee, Way Seah; Yap, S.F.; Looi, L.M. (Wiley, 2007)
Aim: We conducted a prospective study to determine the role of alpha 1-antitrypsin (alpha 1AT) deficiency in the pathogenesis of neonatal cholestasis and other childhood liver diseases in a multi-ethnic Southeast Asian population. Methods: Prospective patients with neonatal cholestasis (group 1), other liver diseases (group 2) and children with other medical conditions (group 3) referred to the Paediatric Unit, University of Malaya Medical Centre, Malaysia, from May 2002 to June 2005, were screened for alpha 1AT level and phenotype. alpha 1AT level below 80 mg/dL was considered as low. Results: Of the 114 patients (group 1, n = 53; group 2, n = 42; group 3, n = 19) screened, seven patients (6 of total; group 1, n = 1; group 2, n = 4; group 3, n = 2) had a alpha 1AT level below 80 mg/dL. All had marginally low level (range 57-79 mg/dL), but none had a clinical diagnosis of alpha 1AT deficiency. One patient had PiZ- heterozygous phenotype (alpha 1AT level 217 mg/dL) while another patient had PiMS heterozygous. Conclusions: alpha 1AT deficiency is not an important cause of neonatal cholestasis and childhood liver diseases in Malaysian children. In Malaysian children with neonatal cholestasis or other liver diseases, routine assay for alpha 1AT phenotype is not recommended if there is no family history of neonatal cholestasis of uncertain aetiology, or if alpha 1AT level is above 80 mg/dL.